Job Polarization and the Declining Fortunes of the Young : Evidence from the United Kingdom - Dabla-Norris, Era (IMF Working Papers; Working Paper ;, 2019)
This paper uses a life-cycle framework to document new stylized facts about the nexus between job polarization and earnings inequality. Using quarterly labor force data for the UK over the period 2000-2018, we find clear life-cycle profiles in the probability of being employed within each occupation type and wages earned therein. Cohort plots and econometric analysis suggest that labor market outcomes and prospects have gradually worsened for the young. These adverse trends are particularly significant for low-skill women: estimated cohort effects point to a fall in wages within each occupation as well as a lower propensity of being employed in abstract-task occupations. We also find evidence of general occupational downgrading in the UK, with more educated workers taking up fewer high-skill occupations than they did in the past. Our analysis informs the policy debate over appropriate measures needed to reduce skill mismatches and alleviate labor market transitions.